Desenvolvimento de formulações multiparticuladas contendo microescleródios do fungo Metarhizium anisopliae para controle biológico - Santos, Thainá Rodrigues (2016)
Introduction and objective: Metarhizium anisopliae is one of the most studied fungi for biological control, since it is found naturally associated with ticks and has showed high virulence in laboratory conditions. M. anisopliae can form in vitro an overwintering structure called microesclerotia (MS). The microsclerotia have been shown to be more effective than products based on conidia when applied directly to the soil for control of some pests. Thus, the objective of this study was to develop and characterize inorganic pelletized formulations containing microsclerotia of M. anisopliae IP119, assess its stability under storage at 4°C and 40°C and determine its tolerance to UV-B radiation. Methods: Six pellets formulations composed of diatomaceous earth, vermiculite, aluminum magnesium silicate or colloidal silicon dioxide, alone or in combination, were developed and evaluated. The pellets were obtained using the extrusion-spheronization technique and were dried in a fluid-bed dryer with an outlet air temperature kept at 40°C or 50°C. During drying, at pre-determined time intervals, samples were collected for evaluation of the residual moisture content, conidia production and viability. The pellets were also evaluated for their storage stability at 4°C and 40°C. Conidia production and viability were evaluated after storage periods of 7 to 21 days. In addition, UV-B tolerance of the conidia and pellets containing MS was evaluated by exposing them to the artificial light for 4h (irradiance of 541,54 mW/m2) and 12h (irradiance of 1239,23 mW/m2), respectively. Results and Discussion: Inorganic pellets were obtained and the selected formulation was composed by vermiculite, diatomaceous earth and colloidal silicon dioxide (78:20:2), since it showed the best yield (48%), size distribution (from 431.5 to 758.5 μm), average size (584.90 μm ± 122.40) and sphericity (0.75 ± 0.07). There was a considerable reduction of the residual moisture between time 0 (~29%) and 5 minutes (~6%), which remained stable until the end of drying operation. Thus, pellet drying for a 5 minutes period at 40ºC or 50°C resulted in a proper moisture content. Fluid-bed dried pellets presented conidia production always above 1.7x109 conidia/g pellets, with viability > 93%, at all times and for both temperatures. In the pellet storage at 40°C, a contamination was observed after the 7th storage day, without differences in conidia production (~1.3x109 conidia/g of pellets) and viability (> 94%). At 4°C, the conidia production and viability remained stable until the 21th storage day. Regarding the tolerance to UV-B radiation test, the calculated LD50 of M. anisopliae conidia was 5.545 (kJ/m2) ± 0.059. In the exposed pellets containing microsclerotia germination was >98%, and it was observed high conidia production (>1,6x109 conidia/g of pellets). Conclusion: It can be concluded that the inorganic formulation allow to obtain pellets containing fungal material by extrusion-spheronisation technique with maintenance of fungal viability after drying, resulting in a formulation with high UV-B tolerance. This solid platform has a great potential for use in pest biological control.